Reduced Audit Quality Practices among Local-Government’s Internal Auditors: What to do with Stress and Working Condition - Ariwibowo, Rinto; Nurkholis, Nurkholis; Saraswati, Erwin (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 18 No 1 (2023), 2023)
This study aims to reveal the influence and effect of stress and its ?predecessor through ?the lens of Job-Demand ?Resource Theory (JD-R). ?This research utilizes the quality of working life and work ?interference with personal life as ?predictors of stress and reduced audit quality practice. ?The ?subjects of ?this study involved 326 local government internal auditors in Bali ??Area. Quantitative analysis using PLS-SEM demonstrated both ?predictors’ effects in ?forming auditor’s stress. The study also confirms ?that stress mediates the ?formation of reduced audit quality ?practices among auditors. The result of the study is ?expected to give ?strategic recommendations to Government ?Internal Control Apparatus/ Aparat Pengawasan Intern Pemerintah ??(APIP) management to promote better stress ?management and work-life balance programme, expecting ?to prevent dysfunctional audit practices while optimizing their ?audit quality. Keywords: job demand resource theory, quality of working life, work ?interference with personal life, job stress, reduced audit quality practice